The acute effect of maximal voluntary isometric contraction pull on start gate performance of snowboard and ski cross athletes - Haycraft, J. A. Z.; Gastin, P. B.; Robertson, S. (International Journal of Sports Science & Coaching, 2016)
This study investigated whether adding a maximal voluntary isometric contraction to developing snowboard and ski cross athletes` warm-up could reduce start time. A secondary aim was to assess the appropriateness of start performance as a talent identification tool for junior athletes by determining whether differences in time could be explained by participant age and anthropometry. Twenty sub-elite athletes (male: n=11, female: n=9, age: 15.0±1.4 years) participated. No differences were found for start time (7.5m) between maximal voluntary isometric contraction and standardised (no-maximal voluntary isometric contraction) warm-up or gender (maximal voluntary isometric contraction; males: 1.36±0.07s, females: 1.41±0.03s, no-maximal voluntary isometric contraction; males: 1.35±0.01s, females: 1.38±0.10s, P>0.05). A strong relationship between body mass and start time to 7.5m (r=0.78, r2=0.61, P<0.05) was observed. Use of maximal voluntary isometric contraction-based warm-ups with developing snowboard cross and ski cross athletes may not be beneficial to improving performance. ABSTRACT FROM AUTHOR